If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -7 = 2 + -5x Reorder the terms: -7 + 9x = 2 + -5x Solving -7 + 9x = 2 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -7 + 9x + 5x = 2 + -5x + 5x Combine like terms: 9x + 5x = 14x -7 + 14x = 2 + -5x + 5x Combine like terms: -5x + 5x = 0 -7 + 14x = 2 + 0 -7 + 14x = 2 Add '7' to each side of the equation. -7 + 7 + 14x = 2 + 7 Combine like terms: -7 + 7 = 0 0 + 14x = 2 + 7 14x = 2 + 7 Combine like terms: 2 + 7 = 9 14x = 9 Divide each side by '14'. x = 0.6428571429 Simplifying x = 0.6428571429
| 3x^2+55+225=0 | | 3x^2+100+225=0 | | 4x^2+100+225=0 | | 5x^2+100+225=0 | | 5x^2+71+443=0 | | 6x+15=16x+4 | | =1607 | | 5x^2+75+250=0 | | 6x^2+75+250=0 | | 6x-4(x-2)=1607 | | 11u-4=7 | | 6x^2+215+300=0 | | 6x^2+50+125=0 | | h=-4.9x^2+40x+1 | | 6x^2+200+308=0 | | 22+4(1-5x)=25-(2x+17) | | 6x^2+215+310=0 | | 6x^2+215+308=0 | | X^2-6x+130=0 | | 9x+4=4x+27 | | 4x-12=2x+24 | | 15x=680 | | 5x-8(x-5)=1607 | | 6x+1=4-(3-11x) | | 2n=48 | | M=15+6h | | 9/10+17/18 | | 4u-6-3u+2=5 | | b+8/7b^2+56b | | -16y=da | | (t/8)-(3/4)=9/16 | | 3dx^2-4dx+d+1=0 |